Broad-spectrum antimicrobial activities of a food fermentate of Aspergillus oryzae - Dasol Choi; Ahmad F. Alshannaq; Yohan Bok; Jae-Hyuk Yu (Microbiology Spectrum)
ABSTRACT Amid persistent concerns over microbial foodborne illnesses and escalating antibiotic resistance, we introduce “NP,” a novel and effective broad-spectrum natural antimicrobial product derived from the filtered culture broth of Aspergillus oryzae grown in a food-grade liquid medium. NP demonstrates potent bactericidal activity against a range of food-borne and ESKPAE pathogens, including Staphylococcus aureus (including eight distinct drug-resistant methicillin-resistant Staphylococcus aureus strains), Listeria monocytogenes, Salmonella typhimurium, Klebsiella pneumonia, Pseudomonas aeruginosa, and Escherichia coli (including O157:H7) with minimal inhibitory strength ranging from 25% to 100%. In addition, NP exhibits robust antifungal activity against several human pathogenic fungi including Aspergillus fumigatus, Candida albicans, and the prevalent food spoilage mold Penicillium species, arresting spore germination and vegetative cell growth. Mechanistically, NP disrupts the structural integrity of bacterial and fungal cell membranes, increasing membrane permeability and leading to cell death. Furthermore, genome-wide expression analyses of A. fumigatus vegetative cells exposed to NP reveal the downregulation of genes associated with the liveness of the fungal cells including ergosterol biosynthesis, cell wall maintenance, and development, with network analysis highlighting NP’s impact on various metabolic pathways. Notably, NP is presumed safe and thermally stable, holding promise for addressing foodborne illnesses and drug-resistant infections through the development and widespread application of a new generation of antimicrobials.IMPORTANCEThe development of NP, a potent broad-spectrum antimicrobial, is a significant breakthrough in the ongoing challenge against microbial foodborne illnesses and the growing threat of antibiotic resistance. This food-grade culture broth of Aspergillus oryzae demonstrates exceptional broad-spectrum efficacy against a variety of harmful bacteria and fungi, including drug-resistant strains such as methicillin-resistant Staphylococcus aureus and prevalent food spoilage molds. NP exhibits strong bactericidal activity against various foodborne and ESKAPE pathogens, and strong antifungal activity against Penicillium species, Aspergillus fumigatus, and Candida albicans. The potent bactericidal and antifungal properties of NP are a result of its ability to disrupt microbial cell membranes leading to increased permeability. Furthermore, the genome-wide impact of NP on fungal gene expression and metabolic pathways underscores its comprehensive antimicrobial action, leading to transcriptomic and metabolic changes associated with cell death in A. fumigatus.